Measurement of the inclusive jet cross-sections in proton-proton collisions at √s=8 TeV with the ATLAS detector - Santos, S. P. Amor dos (2017)
Inclusive jet production cross-sections are measured in proton-proton collisions at a centre-of-mass energy of s=8 TeV recorded by the ATLAS experiment at the Large Hadron Collider at CERN. The total integrated luminosity of the analysed data set amounts to 20.2 fb−1. Double-differential cross-sections are measured for jets defined by the anti-kt jet clustering algorithm with radius parameters of R = 0.4 and R = 0.6 and are presented as a function of the jet transverse momentum, in the range between 70 GeV and 2.5 TeV and in six bins of the absolute jet rapidity, between 0 and 3.0. The measured cross-sections are compared to predictions of quantum chromodynamics, calculated at next-to-leading order in perturbation theory, and corrected for non-perturbative and electroweak effects. The level of agreement with predictions, using a selection of different parton distribution functions for the proton, is quantified. Tensions between the data and the theory predictions are observed.